Analisis Pengaruh Luas Lahan, Tenaga Kerja Dan Jumlah Produksi Tebu Terhadap Produk Domestik Regional Bruto Subsektor Perkebunan Kabupaten Aceh Tengah - Mujiburrahmad Mujiburrahmad; Edy Marsudi; Teuku Fauzi; Keke Putri Anggraini (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
Central Aceh Regency is the largest sugar cane producer in Aceh Province. Land area and labor are production factors which are very important to consider which fluctuate will affect the amount of production. Sugar cane, which is one of the largest commodities in the Central Aceh Regency plantation sub-sector, contributes to the value of gross regional domestic product (GRDP) in the district, so that the fluctuating value of sugar cane production will affect the district's plantation subsector GRDP. The aim of the study was to study the direct or indirect ways between large land, labor, and the amount of sugarcane production in the Central Aceh Regency GRDP plantation sub-sector. The data used are secondary data in the form of sequential time (time series) from 2003-2017. This study uses path analysis with two substructural equations. Based on the results of the study, the substructure of my land area is positive and significant for the amount of sugarcane production while labor affects negatively on the amount of sugarcane production. In substructure II, the area of land and sugar cane labor is not binding on the Central Aceh Regency GRDP Subsector, while the amount of production has a positive effect on the Central Aceh Regency GRDP Subsector. While the area and sugar cane labor do not support the Central Aceh Regency GRDP sub-sector through the amount of sugar cane production.